SUBSIDIARITY DEMOCRACY IN PROCESSES OF GLOBALIZATION AND REGIONALIZATION OF POLITICAL SPACE - Панченко, Т.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article makes an attempt to ground a model of subsidiarsty democracy like one, which provides distributing of powers on different levels of political co-operation, coming from lower level primary rights to actions in contrast to higher levels. This model integrates the elements of global (cosmopolitan), participatory and deliberative democracies as well it corresponds to processes of globalization and regionalization of political space.